PENGARUH PENERAPAN MODEL PEMBELAJARAN TEMATIK DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PENALARAN SISWA MA ISLAMIC CENTRE CIREBON - priyati priyati; Hadi Kusmanto; alif ringga persada (EduMa: Mathematics education learning and teaching, 2015)
Students’ success in learning mathematics can be measured from the learning process. By learning mathematics, it is expected that students can improve their thinking ability that includes the ability to reason, solve problems, communicate, and respect the usefulness of Mathematics. However, preliminary observation had showed that students’ achievement in learning mathematics is relatively low due to conventional methods of instruction. This research aims at; 1) finding out the students' responses to the application of thematically integrated learning in Mathematics, 2) finding out students’ reasoning skills in the composition of the two functions and inverse functions, and 3) finding out the effect of thematically integrated instruction in Mathematics on students’ reasoning ability. It is expected that the implementation of this learning model would improve students’ Mathematic achievement. The results demonstrate a regression equation of Y = 15.477 + 0,714X, a regression coefficient is positive of 0.714. This can be interpreted as a response to the implementation of thematic learning model thet the better it will improve students’ reasoning ability. Number R Square of 0,151. Meaning that the level of reasoning ability of students’ affected by the high and low stundents’ response to the implementation of thematic learning model 15,1%. The implementation of thematic learning model in the study of mathematics can be see from the results of the regression coefficient test showed thet significant value 0,007 < 0,05. Therefore, Ho is rejected. This result illustrates that there is a significant effect of the implementation of thematic learning model in teaching mathematics on students' reasoning ability.Keywords: Thematically Integrated Instruction, Ability, Reasoning